Virtual Reality (VR) Glasses for Oxytocin Relaxation Therapy to Increase Breast Milk Production of Postpartum Mothers - Herlina, Nina; ekowati, Erik; Fratidhina, Yudhia; Nugroho, Widyo; Agustina, Indah Fitri; Aticeh, Aticeh (Jurnal Midpro, 2022)
Background: Breast milk is the best food for newborns until the age of 2 years, but many breastfeeding mothers have difficulty breastfeeding and cause anxiety, stress, and depression. This condition causes the growth of the hormone oxytocin to be slow so that the milk production does not go smoothly. Objective: developing the application of virtual reality (VR) glasses as oxytocin relaxation therapy to increase breast milk production in postpartum mothers. Method: the method used was pre-experimental with a one-group pretest-posttest design approach. Results: This research involved respondents with the criteria; breastfeeding mothers with an age range of 20-35 years, the majority of whom have higher education, most of whom work. The results show that there is a difference in the average before and after treatment with VR glasses, namely the average before treatment was 57.11 with an SD of 13,546, the average after treatment was 73.55 with an SD of 9.921. Statistical test results obtained a p-value of 0.000 (p<) with a difference in the average value of 11.44. The conclusion is that postpartum mothers who are breastfeeding are comforted by the application of audio-visual, thereby stabilizing the increase in the hormone oxytocin which acts as an increase in breast milk production.